Non-perfluoropolymer material, preparation method thereof and application of non-perfluoropolymer material in lithium metal battery

By using 2,2,3,3-tetrafluoropropyl methacrylate (TFM) in lithium metal batteries, the problems of low Li+ conductivity and short cycle life in GPE are solved, and lithium is significantly improved Electrochemical stability and safety performance of the battery.

CN119285843AActive Publication Date: 2025-01-10HENAN UNIVERSITY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411256073.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-01-10
Estimated Expiration
2044-09-09

AI Technical Summary

Technical Problem

The existing crosslinked network gel polymer electrolytes (GPEs) have problems with low Li+ ion conductivity and short cycle life in lithium metal batteries, resulting in low actual energy density and short cycle life, and lack of in-depth understanding of the Li+ conduction mechanism.

Method used

Using 2,2,3,3-tetrafluoropropyl methacrylate (TFM) as a non-perfluoropolymer monomer, it forms weak hydrogen bonds through interaction with lithium salt anions, limits the migration of anions and improves cation migration. Number and ionic conductivity to construct a quasi-solid electrolyte for non-perfluoropolymer materials.

Benefits of technology

It significantly improves the number of ion migration and ion conductivity in PTFM, improves electrochemical/chemical stability, extends the cycle life of lithium batteries, and improves safety performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a non-perfluoropolymer material, a preparation method thereof and an application of the non-perfluoropolymer material in a lithium metal battery, and belongs to the technical field of lithium batteries, lithium salt, a cross-linking agent, a non-perfluoropolymer monomer and an ester solvent are uniformly mixed to obtain a precursor solution, an initiator is added to obtain a non-perfluoropolymer material precursor solution, and the non-perfluoropolymer material precursor solution is subjected to vacuum drying to obtain the non-perfluoropolymer material. Dripping the non-perfluoropolymer material precursor solution on a diaphragm, assembling the diaphragm into a battery, and heating to react completely, so as to generate the non-perfluoropolymer material on the diaphragm in situ; the non-perfluoropolymer monomer is 2, 2, 3, 3-tetrafluoropropyl methacrylate, the cross-linking agent is trimethylolpropane triacrylate, the volume ratio of the non-perfluoropolymer monomer to the cross-linking agent is (1-1000): (1000-1), and the total volume of the cross-linking agent and the non-perfluoropolymer monomer accounts for 1-99% of the volume of the cross-linking agent, the non-perfluoropolymer monomer and the ester solvent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of polymer electrolyte preparation, and specifically relates to a non-perfluorinated polymer material, a preparation method thereof and an application thereof in a lithium metal battery. Background Art

[0002] Lithium (Li) metal has a high theoretical capacity, which is about ten times that of traditional graphite anodes (3860 mAhg -1 vs 372 mAh g -1 ), and is therefore considered to be the most promising negative electrode material for high energy density lithium metal batteries.

[0003] Compared with liquid and all-solid electrolytes, cross-linked network gel polymer electrolytes (GPEs) provide an effective solution for improving the interfacial reaction stability and safety of metal-based batteries with higher theoretical energy density (such as lithium metal batteries and sodium metal batteries). + Ionic conductivity and Li + The transfer number still limits the rate and stability of the chemical reaction at the electrode, resulting in low actual energy density and short cycle life of the battery. In the past few decades, in order to improve the safety of batteries, GPEs such as polycarbonate and polyether have been developed, and better cycle life has been achieved by changing the cross-linked network structure and introducing functional additives. However, improving the ionic conductivity of GPE is still a challenge for building lithium batteries with high energy capacity and long life. + The lack of in-depth understanding of the conduction mechanism and transfer pathway is the reason why it is difficult to improve the electrolyte ion transfer rate.

[0004] This application uses EWG-containing non-perfluorinated monomers (TFM) to form weak hydrogen bonds with anions, clarifies the effect of polymer skeleton regulation on ion transport during ion transport, and significantly improves the ion migration number and ion conductivity in PTFM. It shows excellent electrochemical / chemical stability under long cycles of high-load positive electrodes.

[0005] This application proves for the first time that the formation of intermolecular hydrogen bonds in GPE effectively limits the migration of anions, improves the cation migration number and ionic conductivity. It is worth noting that this study reveals the mechanism of the influence of cation / anion interaction on the ionic conductivity of GPE through "the preparation of a non-perfluoropolymer material", which is of great significance for the development of high-performance and high-safety batteries. Summary of the invention

[0006] In order to solve the deficiencies of the prior art, the purpose of the present invention is to provide a non-perfluoropolymer material, a preparation method thereof and its application in lithium metal batteries. The present invention uses 2,2,3,3-tetrafluoropropyl methacrylate (TFM) molecules as non-perfluoropolymer monomers to construct a quasi-solid electrolyte of non-perfluoropolymer materials, and studies the interaction between the skeleton and lithium salt anions in non-perfluoro electrolyte materials containing electron-withdrawing groups (EWG), limits the ineffective migration of anions, and significantly improves the ion migration number and ion conductivity in PTFM. Excellent electrochemical / chemical stability is demonstrated under long cycles of high-load positive electrodes.

[0007] Based on the above purpose, the present invention adopts the following technical solutions: A method for preparing a non-perfluoropolymer material, the process is as follows: a lithium salt, a cross-linking agent, a non-perfluoropolymer monomer and an ester solvent are uniformly mixed to obtain a precursor solution, an initiator is added to obtain a non-perfluoropolymer material precursor solution, the non-perfluoropolymer material precursor solution is dripped on a diaphragm, the diaphragm dripped with the non-perfluoropolymer material precursor solution is assembled into a battery, and the non-perfluoropolymer material is generated in situ on the diaphragm after heating the diaphragm to complete the reaction; The non-perfluoropolymer monomer is 2,2,3,3-tetrafluoropropyl methacrylate, the cross-linking agent is trimethylolpropane triacrylate, the volume ratio of the non-perfluoropolymer monomer to the cross-linking agent is (1~1000): (1000~1), and the total volume of the cross-linking agent and the non-perfluoropolymer monomer accounts for 1~99% of the volume of the cross-linking agent, the non-perfluoropolymer monomer and the ester solvent.

[0008] Furthermore, the lithium salt is one or more of lithium bis(trifluoromethylsulfonyl)imide (LiN(CF3SO2)2), lithium bis(fluorosulfonyl)imide (LiNF2(SO2)2), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), and lithium difluorooxalatoborate (LiDFOB), and the concentration of the lithium salt in the precursor solution is 0.5~2 mol / L. Preferably, the lithium salt is lithium bis(trifluoromethylsulfonyl)imide (LiN(CF3SO2)2).

[0009] Furthermore, the initiator is one of cyclohexanone peroxide, azobisisobutyronitrile, azobisisoheptylonitrile, and a photoinitiator, and the amount of the initiator added is 0.5~2.0 wt% of the precursor solution. This application uses azobisisobutyronitrile as the initiator.

[0010] Further, the ester solvent is a mixture of two or three of ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), propylene carbonate (PC), and fluoroethylene carbonate (FEC) in any proportion. Preferably, a mixture of two or three of ethylene carbonate (EC), diethyl carbonate (DEC) and fluoroethylene carbonate (FEC) is used as the solvent, and the volume ratio of the three is (1~100): (1~100): (1~100). Specifically, a mixture of diethyl carbonate (DEC) and fluoroethylene carbonate (FEC) in a volume ratio of 4:1 is used as the solvent.

[0011] Furthermore, the heating temperature is 50-70°C, and the heating time is 6-24 h.

[0012] Furthermore, the amount of the non-perfluoropolymer material precursor solution added to the diaphragm is 50-500 μL / cm 2 .

[0013] The non-perfluorinated polymer material is prepared by the above preparation method.

[0014] The above-mentioned non-perfluoropolymer material is used in lithium metal batteries, with lithium as the negative electrode and a substrate coated with a positive electrode active material as the positive electrode. The positive and negative electrodes are separated by a diaphragm dripped with a non-perfluoropolymer material precursor solution. The battery is assembled and packaged, and the reaction is completed by heating.

[0015] The preparation process of the positive electrode is as follows: dissolving the positive electrode active material, the conductive agent and the binder in NMP, and then coating them on the substrate; the conductive agent is one or more of Ketjen black, carbon nanotubes, super P, and conductive carbon black; the positive electrode active material is one or more of lithium iron phosphate, nickel cobalt manganese ternary material 811, nickel cobalt manganese ternary material 622, and nickel cobalt manganese ternary material 532; the binder is one or more of polyvinylidene fluoride, sodium hydroxymethyl cellulose, and polyethylene oxide; the conductive agent accounts for 5-10 wt% of the total weight of the positive electrode active material, the conductive agent and the binder, and the binder accounts for 5-10 wt% of the total weight of the positive electrode active material, the conductive agent and the binder.

[0016] The diaphragm is a glass fiber diaphragm. 50 μL of a non-perfluoropolymer material precursor solution is dripped onto the surface of the glass fiber diaphragm to obtain a diaphragm adsorbed with the non-perfluoropolymer material precursor solution. The diaphragm has a diameter of 16 mm and a thickness of 25 μm after polymerization.

[0017] The substrate can be a common conductive substrate in the battery field, such as aluminum foil, and the electrode area is a commonly used electrode area, such as an area of ​​1.13 cm 2. The positive electrode active material loaded on the substrate can be lithium iron phosphate, nickel cobalt manganese, etc. commonly used in the battery field. There are many choices of conductive agents such as carbon nanotubes, Ketjen black, graphene, and Ketjen black as an example. The preparation process of the lithium iron phosphate positive electrode is as follows: Ketjen black, polyvinylidene fluoride, and lithium iron phosphate are uniformly mixed in N-methyl-2-pyrrolidone, and then evenly pulled on aluminum foil with a four-sided preparation device, and the electrode is heated at 80 ° C and vacuum conditions for 10 hours. The ratio of lithium iron phosphate material, Ketjen black, and polyvinylidene fluoride is 8:1:1. The loading mass of lithium iron phosphate can be selected according to different types of batteries. For example, for 2032 button batteries, the loading amount of lithium iron phosphate is controlled at 20 mg / cm2.

[0018] The preparation process of the nickel-cobalt-manganese 811 positive electrode is as follows: Ketjen black, polyvinylidene fluoride, and nickel-cobalt-manganese 811 are uniformly mixed in N-methyl-2-pyrrolidone, and then uniformly pulled on aluminum foil using a four-sided preparation device, and the electrode is heated at 80°C and vacuum conditions for 10 hours. The ratio of nickel-cobalt-manganese 811 material, Ketjen black, and polyvinylidene fluoride is 8:1:1, and the loading mass of the nickel-cobalt-manganese 811 material can be selected according to different types of batteries. For example, in the case of 2032 button batteries, the low loading amount of the nickel-cobalt-manganese 811 material is controlled at 20 mg / cm2.

[0019] A lithium metal battery made of non-perfluorinated polymer material is obtained by the above method.

[0020] The application of non-perfluoropolymer materials in lithium metal batteries and the unique flame retardant effect of gel polymer electrolyte PTFM significantly improve the safety performance of lithium metal batteries. At the same time, during the cycle, the non-perfluoropolymer monomer material 2,2,3,3-tetrafluoropropyl methacrylate (TFM) as a multifunctional unit forms weak hydrogen bonds through the interaction between EWG and anions in the non-perfluoropolymer; the interaction between lithium ions and anions is weakened, which improves Li + Ionic conductivity promotes uniform deposition of lithium ions and reduces the occurrence of side reactions.

[0021] This application designs and synthesizes a series of cross-linked polyesters with different electron-withdrawing groups (EWG), and can adjust the binding strength between EWG and lithium salt anions. Among them, the interaction between EWG and anions is enhanced to form weak hydrogen bonds; the interaction between lithium ions and anions is weakened, which is Li + The key reason for the improvement of ionic conductivity is that the Li + The maximum transfer number and ionic conductivity are 0.85 and 0.78 mS cm, respectively. −1 , which is much higher than 0.53 and 0.14 mS cm of PMMA without EWG addition. −1The cycle life of Li / / PTFM / / NCM811 battery is 5 times that of Li / / PMMA / / NCM811 battery, and the battery capacity is 5.5 mAh cm −2 In addition, the energy density is 220 Wh kg −1 The capacity retention rate of the graphite / / PTFM / / NCM811 soft-pack battery is 92% after 520 cycles. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Schematic diagram of the structure of monomer and after polymerization; Figure 2 Optical photos of GPE: (a) Photograph of GPE after polymerization, (b) IR spectra of GPE before and after polymerization; Figure 3 GPE electrochemical tests: (a) is the ion conductivity test of GPE, (b) is the ion mobility test of GPE; Figure 4 For MMA, MMA / Li + 、TFM、TFM / Li + Solvent NMR spectrum analysis; Figure 5 Molecular dynamics simulations of GPE (PMMA) and GPE (PTFM): (a, b) GPE with anions (LFSI - ), (c, d) are the binding energies of lithium ions in GPE, (e) is the distance between CH in TFM and CF in TFSI, (f) is the distance between CH in MMA and CF in TFSI, (g) is the radial function distribution of Li-O(TFSI) in GPE, (h) ion diffusion coefficient; Figure 6 Half-cell performance test: (a) Li symmetric battery cycle performance test with a current density of 0.5 mA cm -2 , with a capacity of 2 mAh cm -2 (b) Cyclic performance test of lithium symmetric battery with a current density of 1 mA cm -2 , with a capacity of 1 mAhcm -2 ; Figure 7 Full battery performance test: (a) Long cycle performance test of a battery with lithium iron phosphate as the positive electrode, lithium metal as the negative electrode and GPE, (b) Long cycle performance test of a battery with NCM811 as the positive electrode, lithium metal as the negative electrode and GPE; the red and blue colors above represent the coulombic efficiency of different cycle numbers, and the red and blue colors below represent the cycle capacity of different cycle numbers. Li||LiFePO4 and Li||NCM811 batteries are assembled for comparison. DETAILED DESCRIPTION

[0023] In order to make the technical purpose, technical solution and excellent effects of the present invention clearer, the technical solution of the present invention is further described below in conjunction with the accompanying drawings and specific embodiments.

[0024] Source of materials: Ethyl methyl carbonate (EMC), fluoroethylene carbonate (FEC), liquid electrolyte in a volume ratio of 8:2, lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), all of which were purchased from Suzhou Duoduo Chemical Co., Ltd., China. The water content of the solvent is less than 20 ppm, and the water content of the lithium salt is less than 40 ppm. 2,2,3,3-tetrafluoropropyl methacrylate (TFM), methacrylate (MMA) were purchased from McLean Chemical Company. Lithium iron phosphate, nickel-cobalt-manganese ternary material 811, and Ketjen carbon black were purchased from Cologne. The glass fiber separator is a battery-grade separator, model: Whatman battery separator 1822-090.

[0025] The purity of the argon gas used in the experiment was 99.999%. All materials used for battery assembly were stored in a glove box filled with argon.

[0026] Embodiment 1: A method for assembling a lithium symmetric battery made of non-perfluorinated polymer materials, the process is as follows: (1) Preparation of electrolyte: After the non-perfluoropolymer monomer 2,2,3,3-tetrafluoropropyl methacrylate (TFM) and the crosslinker trimethylolpropane triacrylate (TPA) were mixed uniformly in a volume ratio of 1:1, the mixed solution of the monomer and the crosslinker was mixed uniformly with the ester solvent (volume ratio, EMC:FEC=8:2) in a volume ratio of 1:9, and then LiTFSI and azobisisobutyronitrile (AIBN) were added to make the concentration of LiTFSI in the total liquid of the monomer, the crosslinker and the ester solvent 1 mol / L, to obtain a non-perfluoropolymer electrolyte precursor. The amount of azobisisobutyronitrile added was the total amount of the monomer, the crosslinker and the ester solvent. 0.5% of the total mass; the fluorine-free polymer monomer methacrylate (MMA) and the crosslinker trimethylolpropane triacrylate (TPA) were first mixed evenly in a volume ratio of 1:1, and then the mixed solution of the monomer and the crosslinker was mixed evenly with the ester solvent (volume ratio, EMC:FEC=8:2) in a volume ratio of 1:9, and then LiTFSI and azobisisobutyronitrile (AIBN) were added to make the concentration of LiTFSI in the total liquid of the monomer, crosslinker and ester solvent 1mol / L to obtain a fluorine-free polymer electrolyte precursor. The amount of azobisisobutyronitrile added was 0.5% of the total mass of the monomer, crosslinker and ester solvent. The structures of TFM, TPA and MMA are detailed in Figure 1 .

[0027] (2) Assembly: The battery was assembled in an argon-filled glove box. Lithium was selected as the positive and negative electrodes. The positive and negative electrodes were separated by a glass fiber separator. 50 μL of the non-perfluorinated polymer electrolyte precursor solution or the fluorine-free polymer electrolyte precursor solution prepared in (1) was dropped on the glass fiber separator and then packaged. After packaging, it was heated at 60°C for 6 h (the diameter of the separator was 16 mm and the thickness after polymerization was 25 μm). TFM and TPA in the non-perfluorinated polymer electrolyte precursor polymerized to form PTFM, and MMA and TPA in the fluorine-free polymer electrolyte precursor polymerized to form PMMA. The structures of PTFM and PMMA are detailed in Figure 1 The actual photos of PTFM and PMMA after polymerization are as follows: Figure 2 As shown in (a), the infrared spectra of monomers MMA, TFM and polymerized PMMA and PTFM are as follows: Figure 2 As shown in (b), Figure 2 (a) shows that there is no liquid flow after the polymerized electrolyte is inverted. Figure 2 (b) The infrared spectrum shows that the polymerized electrolyte has a wavelength of 1630 cm -1 The C=C characteristic peak at the position disappears, indicating that the monomer is completely polymerized.

[0028] The ion migration number and ion conductivity of fluorine-free gel polymer electrolyte PMMA and non-perfluorinated gel polymer electrolyte PTFM were tested at room temperature. Figure 3 As shown in Figure 2, at room temperature, the ion migration number of PMMA, a fluorine-free gel polymer electrolyte, is 0.53 and 0.14 mS cm -1 The ionic conductivity, ion transfer number and ionic conductivity of the non-perfluorinated gel polymer electrolyte PTFM containing EWG are 0.85 and 0.78 mS cm -1 .

[0029] The NMR spectra of the mixed solvents formed by adding LiTFSI to MMA and TFM solvents (the concentration of LiTFSI in the solvent was 1 mol / L) were analyzed by NMR. Figure 4 It can be seen that the present application has found that, unlike the H chemical environment in MMA, there is an interaction between the H in -CF2CF2H and TFSI in TFM, causing its chemical shift to shift to a high field.

[0030] The molecular dynamics simulations of GPE(PMMA) and GPE(PTFM) are shown in Figure 5Through molecular dynamics simulation, it was found that the distance between CH in TFM and CF in TFSI was only 3.8 Å, which is a weak hydrogen bond. It was further concluded that by adjusting the binding strength between EWG and lithium salt anions to form weak hydrogen bonds, the interaction between lithium ions and anions was affected, thereby increasing the Li ion migration number and ionic conductivity.

[0031] At room temperature, the current density was 0.5 mA cm -2 , with a capacity of 2 mAh cm -2 and a current density of 1 mA cm -2 , with a capacity of 1 mAh cm -2 The battery performance was tested below, and the results are shown in Figure 6 .like Figure 6 As shown, at 1 mA cm -2 Current density and 1 mAh cm -2 The Li||PTFM||Li battery can operate stably for more than 1800 h at a capacity of 0.5 mA cm. In comparison, the Li||PMMA||Li symmetric battery operates for 400 h. -2 Current density and 2 mAh cm -2 At the same time, the Li||PTFM||Li battery can run stably for more than 2000 hours. In contrast, the Li||PMMA||Li symmetric battery can only run for less than 400 hours. The reason for its good cycle stability is mainly due to the higher ion migration number and ion conductivity of PTFM, and the uniform deposition during the lithium ion cycle, thereby inhibiting the occurrence of side reactions.

[0032] Embodiment 2: A method for assembling a lithium-lithium iron phosphate battery made of non-perfluorinated polymer materials, the process is as follows: (1) Preparation of positive electrode: lithium iron phosphate material, polyvinylidene fluoride, and ketjen black were uniformly mixed in N-methyl-2-pyrrolidone in a mass ratio of 8:1:1, and then uniformly stretched on aluminum foil using a four-sided preparation device. The electrode was heated at 80°C under vacuum for 10 h. The loading mass of lithium iron phosphate was controlled to be ~20 mg / cm2. (2) Preparation of electrolyte: same as step (1) in Example 1.

[0033] (3) Take 50 μL of the non-perfluorinated polymer electrolyte precursor solution or the fluorine-free polymer electrolyte precursor solution prepared above and drop it on the glass fiber separator; (4) Assembly: The battery was assembled in a glove box filled with argon gas. Lithium was selected as the negative electrode. The positive electrode and the negative electrode were separated by the glass fiber separator in step (3). After assembly, the battery was packaged and heated at 60°C for 6 h. The battery performance was tested at room temperature.

[0034] Embodiment 3: A method for assembling a lithium-ternary nickel-cobalt-manganese 811 battery made of non-perfluorinated polymer materials, the process is as follows: (1) Preparation of positive electrode: The ternary nickel-cobalt-manganese 811 material, polyvinylidene fluoride, and ketjen black were uniformly mixed in N-methyl-2-pyrrolidone in a mass ratio of 8:1:1, and then evenly stretched on aluminum foil using a four-sided preparation device. o C. Heating under vacuum for 10 h, the loading mass of ternary NiCoMn 811 was controlled to 20 mg / cm2; (2) Preparation of electrolyte: same as step (1) in Example 1.

[0035] (3) Take 50 μL of the non-perfluorinated polymer electrolyte precursor solution or the fluorine-free polymer electrolyte precursor solution prepared above and drop it on the glass fiber separator; (4) Assembly: The battery was assembled in a glove box filled with argon gas. Lithium was selected as the negative electrode. The positive electrode and the negative electrode were separated by the glass fiber separator in step (3). After assembly, the battery was packaged and heated at 60°C for 6 h. The battery performance was tested at room temperature.

[0036] Assembly of different types of batteries: The batteries were assembled in a glove box filled with argon gas, with lithium as the negative electrode, and a glass fiber separator with or without nitrogen electrolyte between the positive and negative electrodes. After assembly, button CR 2032 batteries were used for packaging. All batteries were tested in a constant temperature box.

[0037] The performance of the battery prepared in Example 2 with lithium iron phosphate as the positive electrode, lithium metal as the negative electrode and GPE as the negative electrode and the battery prepared in Example 3 with NCM811 as the positive electrode, lithium metal as the negative electrode and GPE as the negative electrode were tested. The results are shown in Figure 7 ,Depend on Figure 7 It can be seen that under high load, the battery assembled with PTFM as electrolyte and lithium iron phosphate as positive electrode can stably cycle 650 cycles, and the battery assembled with NCM811 battery as positive electrode can stably cycle 280 cycles. In contrast, the battery assembled with PMMA as electrolyte and lithium iron phosphate as positive electrode has a significant capacity decay after 200 cycles, and the battery assembled with NCM811 battery as positive electrode has a significant capacity decay after 100 cycles.

[0038] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a non-perfluorinated polymer material, characterized in that: The process is as follows: The lithium salt, the cross-linking agent, the non-perfluoropolymer monomer and the ester solvent are uniformly mixed to obtain a precursor solution, an initiator is added to obtain a non-perfluoropolymer material precursor solution, the non-perfluoropolymer material precursor solution is dripped on the diaphragm, the diaphragm dripped with the non-perfluoropolymer material precursor solution is assembled into a battery, and the non-perfluoropolymer material is generated in situ on the diaphragm after the reaction is completed by heating; The non-perfluoropolymer monomer is 2,2,3,3-tetrafluoropropyl methacrylate, the cross-linking agent is trimethylolpropane triacrylate, the volume ratio of the non-perfluoropolymer monomer to the cross-linking agent is (1~1000): (1000~1), and the total volume of the cross-linking agent and the non-perfluoropolymer monomer accounts for 1~99% of the volume of the cross-linking agent, the non-perfluoropolymer monomer and the ester solvent.

2. The method for preparing a non-perfluorinated polymer material according to claim 1, characterized in that: The lithium salt is one or more of lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium tetrafluoroborate, lithium bis(trifluoromethylsulfonyl)imide, and lithium bis(fluorosulfonyl)imide, and the concentration of the lithium salt in the precursor solution is 0.5-2 mol / L.

3. The method for preparing a non-perfluorinated polymer material according to claim 1, characterized in that: The initiator is one or more of cyclohexanone peroxide, azobisisobutyronitrile, azobisisoheptanenitrile, and a photoinitiator, and the added amount of the initiator is 0.5-2.0wt% of the precursor solution.

4. The method for preparing a non-perfluorinated polymer material according to claim 1, characterized in that: The ester solvent is a mixture of two or three of ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), propylene carbonate (PC) and fluoroethylene carbonate (FEC) in any proportion.

5. The method for preparing a non-perfluorinated polymer material according to claim 1, characterized in that: The heating temperature is 50~70℃ and the heating time is 6~24 h.

6. The method for preparing a non-perfluorinated polymer material according to claim 1, characterized in that: The amount of non-perfluoropolymer material precursor solution added to the diaphragm is 50~500μL / cm 2 .

7. The non-perfluorinated polymer material obtained by the preparation method according to any one of claims 1 to 6.

8. Use of the non-perfluorinated polymer material according to claim 7 in a lithium metal battery, characterized in that: Lithium is used as the negative electrode, and a current collector coated with a positive electrode active material is used as the positive electrode. The positive electrode and the negative electrode are separated by a diaphragm dripped with a non-perfluoropolymer material precursor solution. The assembly is completed and packaged, and the heating reaction is completed to obtain the product.

9. The use according to claim 8, characterized in that The preparation process of the positive electrode is as follows: dissolving a positive electrode active material, a conductive agent, and a binder in NMP, and then coating the positive electrode active material on a substrate; the conductive agent is one or more of Ketjen black, carbon nanotubes, super P, and conductive carbon black; the positive electrode active material is one or more of lithium iron phosphate, nickel cobalt manganese ternary material 811 (NCM811), nickel cobalt manganese ternary material 622, and nickel cobalt manganese ternary material 532; the binder is one or more of polyvinylidene fluoride, sodium hydroxymethyl cellulose, and polyethylene oxide; the conductive agent accounts for 5-10 wt% of the total weight of the positive electrode active material, the conductive agent, and the binder, and the binder accounts for 5-10 wt% of the total weight of the positive electrode active material, the conductive agent, and the binder.

10. The use according to claim 8, characterized in that The diaphragm is a glass fiber diaphragm, and the substrate is an aluminum foil.

Citation Information

Patent Citations

  • Polymer for fuel cell proton exchange membrane and preparation method thereof

    CN113683726A

  • Precursor solution of in-situ polyelectrolyte and solid-state battery prepared from precursor solution

    CN117199515A

  • In-situ polymerization solid-state electrolyte precursor solution and solid-state battery

    CN118063692A

  • Lithium metal battery and preparation method thereof

    CN118248957A

  • Preparation method of lithium battery, quasi-solid-state composite electrolyte of lithium battery and lithium battery

    CN118472414A